A Child is Being Caged: Resignation Syndrome and the Psychopolitics of Petrification. (June 2020) - Butler, Daniel G.
Uppgivenhetssyndrom, or resignation syndrome (RS), is a disorder that until recently was thought to affect the children of refugees in Sweden alone. The heuristic of psychopolitics is used to theorize RS as a form of abjection (Bataille, Kristeva) and petrification (Fanon, Marriott), and the movement from petrification to petrification in hallucinosis (Fanon, Bion) is delineated: first these children are petrified by persecutory and culturally specific stereotypes that precede and exceed them symbolically, and then, through a succession of shocks, they enter a post-traumatic stupor in which the faltering symbolization of the stereotype gives way to the (dis)embodiment of abject thinghood. Marriott's distinction between mirror as mask and mask as mirror allows the attribution of RS not only to sociocultural mimesis and the psychosocial impact of stereotypes (mirror as mask) but also to a socially imposed absence that the stereotype simultaneously conceals and reveals (mask as mirror). RS ( petrification in hallucinosis ) is considered the (dis)embodiment of this socially imposed absence.